A Novel Protein Sourced from Chinese Medicine Residue for Golden Pompano Feed: Endothelium Corneum Gigeriae Galli Residue (ECGGR) - Ziqiao Wang; Rong Yao; Xuanshu He; Xin Cui; Zhihong Liao; Yantao Liu; Hanlin Wei; Zhenxiao Zhuang; Mengdie Chen; Jin Niu (Aquaculture Nutrition, 2024)
Fishmeal is an important protein source in aquafeed. However, due to the limited natural resources, fishmeal is in short supply, resulting in a price surge for fishmeal. Here, we reported a kind of Chinese medicine residue, endothelium corneum gigeriae galli residue (ECGGR), as a fishmeal substitute in the diets of Trachinotus ovatus. Six isonitrogenous and isolipidic diets were formulated, substituting fishmeal at 0%, 6.25%, 12.5%, 18.75%, 25%, and 31.25%. There was no significant difference in the growth performance when the fishmeal substitution level was no more than 25%. The smallest FCR was obtained at the 18.75% substitution level. Furthermore, substituting ECGGR for fishmeal had no effect on whole-body and muscle proximate compositions, except when the replacement level exceeded 25%, which led to a decrease in whole-body moisture and an increase in whole-body crude protein. The contents of Gly, Cys, Ile, Tyr, Pro, and EAAs/TAAs were altered as the substitution level varied. However, dietary replacement of fishmeal with ECGGR did not degrade muscle protein quality, according to a nutritional evaluation of muscle essential amino acid composition. In terms of hepatic antioxidant capacity, neither the overall antioxidant status nor the expression of genes in the Nrf2-ARE pathway was altered by dietary ECGGR. Moreover, the expressions of p65, TNF-α, and IL-8 in the intestine were upregulated at the 31.25% substitution level. Also, more goblet cells were observed in the intestine at substitution levels of 25% and 31.25%. In conclusion, ECGGR can substitute for fishmeal at the optimal level of 18.75% without adversely affecting the growth performance, protein quality, or hepatic and intestinal health of golden pompano.